Association between area deprivation index and concerns to COVID-19: A multi-level analysis of individual and area factors - Doo Woong Lee; Jieun Jang; Jaeyong Shin (Elsevier, 2024)
Background: The coronavirus disease 2019 (COVID-19) pandemic has been one of the most serious global threats to public health recently. The present study examined whether area deprivation is associated with concerns related to COVID-19 using large nationwide data across South Korea. Methods: We used nationwide 2020 Korea Community Health Survey and official government database. Of the 225,680 included participants, 123,324 (54.6%) were women, and the mean age was 54.9 [17.8] years old. We classified the Area deprivation index (ADI) into Quartile 1 (Least deprived); Quartile 2; Quartile 3; and Quartile 4 (Most deprived). Our primary outcome was the concerns related to COVID-19 (0-16 scores). Multilevel regression analysis was conducted. Results: The mean score of concerns related to COVID-19 was 11.3 [3.2] in the total population. 13.5% of the variability in the scores of concerns related to COVID-19 was accounted for by district areas. Area with Q4 of ADI were associated with an increased score of concerns related to COVID-19 (Q1: reference; Q2: β = 0.218, SE = 0.119, FDR adj.p-value = 0.085; Q3: β = 0.235, SE = 0.133, FDR adj.p-value = 0.094; Q4: β = 0.252, SE = 0.109, FDR adj.p-value = 0.029). 19-49 groups in area with Q4 of ADI were associated with an increase in scores of concerns related to COVID-19 than other age groups in area with Q4 of ADI. Area with Q4 of ADI were associated with a score of concern of being criticized if getting infected compared to area with Q1 of ADI. Conclusion: We found that the highest quartile ADI was associated with greater concerns related to COVID-19. By identifying vulnerable population to concerns related to COVID-19, health systems may consider preventive intervention to mitigate mental health issues.